Bidirectional association between asthma and migraines in adults: Two longitudinal follow-up studies - Kim, So Young; Min, Chanyang; Oh, Dong Jun; Lim, Jae-Sung; Choi, Hyo Geun (Scientific reports, 2019)
The objective of this study was to evaluate the bidirectional association between asthma and migraines using control subjects matched by demographic factors. The Korean Health Insurance Review and Assessment Service - National Sample Cohort from 2002 to 2013 was used. In study I, 113,059 asthma participants were matched with 113,059 control I participants. In study II, 36,044 migraine participants were matched with 114,176 control II participants. The hazard ratios (HRs) of migraines in the asthma patients (study I) and asthma in the migraine patients (study II) were analyzed using stratified Cox proportional hazard models after adjusting for depression and the Charlson comorbidity index. In study I, 5.3% (6,017/ 113,059) of the asthma group and 3.4% (3,806/ 113,059) of the control I group had migraines (P < 0.001). The asthma group demonstrated an adjusted HR of 1.47 for migraine (95% confidence interval (CI) = 1.41–1.53, P < 0.001). In study II, 15.4% (5,548/36,044) of the migraine group and 10.6% (15,271/144,176) of the control group had asthma (P < 0.001). The migraine group showed an adjusted HR of 1.37 for asthma (95% CI = 1.33–1.41, P value < 0.001). Asthma and migraines are reciprocally associated.